Psychotherapy and art - Andrade Rodríguez, Ricardo Alberto (Poiésis, 2009)
The psychology, in addition to his youth as a recognized discipline, presents a demarcation of its subject of study always controversial. Since the beginning of his definitive separation of philosophy, in the late nineteenth century, its object of study has mutated with the relentless steps of the psychological models: awareness, unconscious, cognitive processes, objetal relationships, the archetype, the behavior.